Mortar material applied to sound insulation and heat preservation of floor slab and preparation method of mortar material
By using mortar materials with specific components in the floor slabs, the cracking and delamination problems of the multi-layer composite floor slabs were solved, better impact sound insulation and material strength were achieved, and the crack resistance and durability of the floor slabs were improved.
Patent Information
- Application Number
- CN202510808473.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-17
- Publication Date
- 2025-09-23
AI Technical Summary
Existing multi-layer composite floor slabs are prone to cracking, delamination and other problems during use, resulting in poor crack resistance and durability.
A mortar material containing components such as silicate cement, aerated concrete particles, polystyrene particles, and composite short fibers is used. Through the synergistic effect of each component, the sound insulation effect and bonding strength of impact sound are improved, a continuous gradation structure is formed to enhance the sound absorption performance, and nano-silica particles are used to enhance the mechanical bite force.
It improves the impact sound insulation effect of the floor and the bonding strength of the material, enhances the crack resistance and durability, and meets the sound insulation requirements of green building specifications.
Smart Images

Figure BDA0005453304760000151 
Figure BDA0005453304760000152
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of floor slab mortar materials, and in particular to a mortar material used for sound insulation and heat preservation of floor slabs and a preparation method thereof. Background Art
[0002] Floor slabs are horizontal structural members used to separate upper and lower spaces in multi-story buildings. They bear loads and transmit forces. In addition to bearing and transmitting vertical and horizontal loads, they also provide a degree of sound insulation, fire protection, and waterproofing. Floor slab sound insulation is a crucial component of building acoustic design. Unlike airborne sound insulation provided by walls, floor slab sound insulation aims to reduce the impact of solid-borne sound on the living environment caused by impact, vibration, and other factors.
[0003] While traditional building sound insulation materials offer good airborne sound insulation performance, their standardized impact sound pressure levels often fail to meet green building standards. For example, GB / T 50118-2010, "Code for Sound Insulation Design of Civil Buildings," requires that individual floor slabs achieve a sound insulation standard of ≥53dB. Currently, a multi-layered approach is often used to enhance floor slab sound insulation. For example, patent publication number CN119411773A proposes a composite thermal insulation and sound-insulating floor system and its construction method. The system comprises a floor base, surrounded by building walls, a sound-reflecting facade within the building walls above the floor base, a first sound insulation layer disposed on the top surface of the floor base, a sound-guiding layer disposed on top of the first sound insulation layer, a second sound insulation layer disposed above the sound-guiding layer, and a thermal insulation layer disposed above the second sound insulation layer. By combining multiple layers of materials with different performance characteristics, the floor slab achieves superior overall sound absorption.
[0004] However, in existing multi-layer composite sound insulation floors such as the above-mentioned ones, in order to meet the load-bearing performance of the floor, it is usually necessary to lay a hardening layer, etc., and such multi-level structural floors are prone to cracking and delamination between different layers as time goes by, that is, the overall crack resistance and durability of the floor are poor. Summary of the Invention
[0005] The purpose of the present invention is to solve the problem that the floor slabs currently made of multi-layer composite materials are prone to cracking and delamination between different layers over time, resulting in poor crack resistance and durability of the overall floor slabs.
[0006] The present invention is achieved through the following technical solutions:
[0007] The present invention provides a mortar material for sound insulation and heat preservation of floor slabs. The mortar material comprises, by mass fraction, 250-350 parts of silicate cement, 100-150 parts of fine sand, 80-120 parts of aerated concrete particles, 50-80 parts of expanded perlite, 30-50 parts of polystyrene particles, 8-12 parts of redispersible latex powder, 1-5 parts of composite short fibers, 0.5-1 part of a water reducer, and 0.3-0.5 part of cellulose. The particle size of the aerated concrete particles is 0.5-5 mm, and the particle size of the polystyrene particles is 1-3 mm.
[0008] Preferably, the polystyrene particles are made from polystyrene masterbatch that has undergone surface strengthening treatment, and the preparation method comprises the following steps:
[0009] The polystyrene masterbatch is immersed in a silane coupling agent aqueous solution and ultrasonically treated; after being taken out and drained, a polyvinyl alcohol aqueous solution is sprayed on the surface and solidified into a film to obtain the polystyrene particles.
[0010] Preferably, the composite staple fibers include polypropylene fibers and basalt fibers, and the length of the polypropylene staple fibers is 3-6 mm, and the length of the basalt fibers is 8-12 mm.
[0011] Preferably, the mass ratio of polypropylene fiber to basalt fiber is 1:1-3.
[0012] The present invention provides a method for preparing the above-mentioned mortar material for floor sound insulation and thermal insulation, comprising the following steps:
[0013] S1 Mix silicate cement, fine sand, cellulose and water reducer according to the amount and stir the dry powder;
[0014] S2 then adds aerated concrete particles, expanded perlite particles and polystyrene in sequence while stirring, and continues stirring after the addition is completed;
[0015] S3 then adds the redispersible latex powder and composite short fibers and stirs;
[0016] Finally, S4 adds nano-silicon dioxide particles and stirs to obtain the mortar material used for floor sound insulation and heat preservation.
[0017] Preferably, in step S2, the aerated concrete particles are pre-treated as follows before being added: the aerated concrete particles are crushed and sieved, and then calcined at 500-700°C for 0.5-2h for standby use.
[0018] Preferably, in step S2, the polystyrene is pretreated as follows before being added: polystyrene particles are impregnated with silica sol, dried to form a film, and then set aside.
[0019] Preferably, in step S4, the nano-silicon dioxide particles account for 1-3% of the total material mass.
[0020] The technical solution of the present invention has the following beneficial effects:
[0021] The mortar material proposed in the present invention for floor sound insulation and heat preservation introduces specific material components such as aerated concrete particles and polystyrene particles to target the special impact sounds between floors of the floor slab. Through the synergistic effect of the various components, the sound insulation effect of the mortar material against the impact sounds and the bonding strength during use are improved as a whole.
[0022] Specifically, aerated concrete particles can reduce density while ensuring support, providing certain impact sound insulation performance, lowering thermal conductivity and achieving a thermal insulation effect. Polystyrene particles can improve micro-elasticity and support, reducing the risk of damage to the aerated layer, thereby more effectively absorbing impact sound. Combining these two, the porous structure of aerated concrete particles can reduce the density of the material system while enhancing the micropore damping effect, capable of absorbing medium and low-frequency impact sound energy. Aerated concrete particles of different particle sizes mixed with polystyrene particles can form a continuously graded structure of "large pores filling small pores," enhancing the mortar material system's absorption and sound absorption of sound waves in different frequency bands.
[0023] In addition, cellulose can control the hardening speed of cement, avoid hollowing between the mortar and the aerated layer, and avoid cracking due to strength differences; expanded perlite is lightweight and infinitely resistant, which can reduce the density of the mortar and provide a certain degree of elasticity and sound insulation performance; composite short fibers are mixed by fibers of different lengths to form a three-dimensional network structure. The shorter polypropylene fibers inhibit plastic shrinkage cracks, and the longer basalt fibers enhance the energy dissipation capacity under impact loads and improve the fracture energy of the mortar material; after the above raw materials are compounded, nano-scale particles are added, and the high activity of nano-silica particles is used to fill the micropores between the polystyrene particles and the matrix to form a dense interface structure. The nano-silica particles enhance the mechanical bite force through the "bridging effect" and improve the flexural strength of the mortar material system. DETAILED DESCRIPTION
[0024] To make the objectives, technical solutions, and advantages of the embodiments of the present invention more clear, the technical solutions in the embodiments of the present invention are described clearly and completely below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed; and where the manufacturers of the instruments, equipment, reagents, and raw materials used are not specified, they are all commercially available conventional products.
[0025] The present invention provides a mortar material for sound insulation and heat preservation of floor slabs, which comprises the following components, calculated by weight: 250-350 parts of silicate cement, 100-150 parts of fine sand, 80-120 parts of aerated concrete particles, 50-80 parts of expanded perlite, 30-50 parts of polystyrene particles, 8-12 parts of redispersible latex powder, 1-5 parts of composite short fibers, 0.5-1 part of a water reducer, and 0.3-0.5 parts of cellulose;
[0026] Among them, the particle size of fine sand is 2-8mm, the particle size of aerated concrete particles is 0.5-5mm, and the particle size of polystyrene particles is 1-3mm; the dry density of aerated concrete particles is ≤800kg / m 3 , the bulk density of polystyrene particles ≤15kg / m 3 The two can achieve the effects of lightweight and high elasticity through synergistic effect.
[0027] In the present invention, the porous structure of aerated concrete particles can reduce the density of the material system, while improving the micropore damping effect, and can absorb medium and low frequency impact sound energy; and aerated concrete particles of different particle sizes are mixed with polystyrene particles, etc. to form a continuous graded structure of "large pores filling small pores", thereby enhancing the absorption and sound absorption effect of the mortar material system on sound waves of different frequency bands.
[0028] In the present invention, the polystyrene particles are prepared by surface strengthening treatment of polystyrene masterbatch, and the specific treatment steps are as follows:
[0029] Take polystyrene masterbatch, immerse it in a silane coupling agent aqueous solution with a mass concentration of about 2%, and ultrasonically treat it for 5-20 minutes to form a hydrophobic-hydrophilic transition layer on its surface; take it out and drain it, spray a polyvinyl alcohol aqueous solution with a mass concentration of 5% on the surface, solidify it into a film, and obtain polystyrene particles.
[0030] Polyvinyl alcohol is coated on the surface of polystyrene particles to form a flexible polymer film on the particle surface, thereby enhancing the chemical bonding strength between the polystyrene particles and the hydration products of the cement mortar and reducing the stratification of the mortar material system.
[0031] In the present invention, the composite short fibers can be made by mixing polypropylene fibers and basalt fibers in a mass ratio of 1:1-3, wherein the length of the polypropylene short fibers is 3-6 mm, and the length of the basalt fibers is 8-12 mm, forming a three-dimensional network structure. The shorter polypropylene fibers inhibit plastic shrinkage cracks, and the longer basalt fibers enhance the energy dissipation capacity under impact loads, thereby improving the fracture energy of the mortar material.
[0032] The preparation method of the mortar material for floor sound insulation and heat preservation of the present invention comprises the following steps:
[0033] (1) Pretreatment:
[0034] First, crush and screen the aerated concrete particles, then calcine them at 500-700℃ for 0.5-2h to remove surface impurities and enhance pore stability before use;
[0035] Separately, polystyrene particles are impregnated with silica sol having a mass concentration of 3-8 wt% for 10-30 minutes and then dried to form a surface waterproof protective layer, thereby reducing the risk of collapse due to water absorption.
[0036] (2) Mix silicate cement, fine sand, cellulose and water reducer according to the amount, and stir the dry powder for 2-10 minutes;
[0037] Then, under the stirring state of 120-200r / min, add aerated concrete particles, expanded perlite and polystyrene particles in sequence, and continue stirring for 2-10 minutes after the addition is completed;
[0038] Then add redispersible latex powder and composite short fibers and stir for 5-30 minutes;
[0039] Finally, add 1-3% of the total material mass of nano-silica particles and stir for 10-20 minutes to obtain a mortar material used for floor sound insulation and thermal insulation. This process uses the high activity of nano-silica particles to fill the micropores between polystyrene particles and the matrix to form a dense interface structure. Nano-silica particles enhance the mechanical bite force through the "bridging effect" and improve the flexural strength of the mortar material system.
[0040] Example 1
[0041] Step 1: Take a polystyrene masterbatch with a particle size of about 1.5±0.2mm, immerse it in a silane coupling agent KH550 aqueous solution with a mass concentration of 2wt% by volume, ultrasonically treat it for 10 minutes, then take it out and drain it, and then spray a polyvinyl alcohol aqueous solution with a mass concentration of 5wt% on its surface, place it at 80℃ and cure it for 20 minutes to obtain polystyrene particles with a particle size of about 2.1±0.1mm.
[0042] Step 2: Take aerated concrete particles with a particle size of about 4±0.5mm, pass them through a 5-mesh sieve, and then place them at 600±10℃ for 1h, cool them and set them aside; take polystyrene particles, immerse them in silica sol for 20min, take them out and dry them for later use.
[0043] Step 3: Take 300 parts by mass of silicate cement, 120 parts by mass of fine sand, 100 parts by mass of aerated concrete particles, 60 parts by mass of expanded perlite, 40 parts by mass of polystyrene particles, 10 parts by mass of ethylene vinyl acetate, 3 parts by mass of composite staple fibers, 0.5 parts by mass of water reducer and 0.4 parts by mass of hydroxypropyl methylcellulose ether as raw materials for use; wherein the composite staple fibers include equal masses of 3 mm long polypropylene staple fibers and 10 mm long basalt fibers.
[0044] Step 4: Mix silicate cement, fine sand, hydroxypropyl methyl cellulose ether and water reducer, and stir in a dry powder state for 5 minutes; then add aerated concrete particles, expanded perlite and polystyrene particles in sequence while stirring at a speed of 145 r / min, and continue stirring for 5 minutes after adding the materials; then add ethylene vinyl acetate and composite short fibers, and stir for 10 minutes; finally, add 2% of the total mass of the above raw materials, and stir for 15 minutes to obtain a floor mortar material.
[0045] Example 2
[0046] Step 1: Take a polystyrene masterbatch with a particle size of about 1.5±0.2mm, immerse it in a silane coupling agent KH550 aqueous solution with a mass concentration of 2wt% by volume, ultrasonically treat it for 10 minutes, then take it out and drain it, and then spray a polyvinyl alcohol aqueous solution with a mass concentration of 5wt% on its surface, place it at 80℃ and cure it for 20 minutes to obtain polystyrene particles with a particle size of about 2.1±0.1mm.
[0047] Step 2: Take aerated concrete particles with a particle size of about 4±0.5mm, pass them through a 5-mesh sieve, and then place them at 600±10℃ for 1h, cool them and set them aside; take polystyrene particles, immerse them in silica sol for 20min, take them out and dry them for later use.
[0048] Step 3: Take 300 parts by mass of silicate cement, 120 parts by mass of fine sand, 85 parts by mass of aerated concrete particles, 60 parts by mass of expanded perlite, 32 parts by mass of polystyrene particles, 10 parts by mass of ethylene vinyl acetate, 3 parts by mass of composite staple fibers, 0.5 parts by mass of water reducer and 0.4 parts by mass of hydroxypropyl methylcellulose ether as raw materials for use; wherein the composite staple fibers include equal masses of 3 mm long polypropylene staple fibers and 10 mm long basalt fibers.
[0049] Step 4: Mix silicate cement, fine sand, hydroxypropyl methyl cellulose ether and water reducer, and stir in a dry powder state for 5 minutes; then add aerated concrete particles, expanded perlite and polystyrene particles in sequence while stirring at a speed of 145 r / min, and continue stirring for 5 minutes after adding the materials; then add ethylene vinyl acetate and composite short fibers, and stir for 10 minutes; finally, add 2% of the total mass of the above raw materials, and stir for 15 minutes to obtain a floor mortar material.
[0050] Example 3
[0051] Step 1: Take a polystyrene masterbatch with a particle size of about 1.5±0.2mm, immerse it in a silane coupling agent KH550 aqueous solution with a mass concentration of 2wt% by volume, ultrasonically treat it for 10 minutes, then take it out and drain it, and then spray a polyvinyl alcohol aqueous solution with a mass concentration of 5wt% on its surface, place it at 80℃ and cure it for 20 minutes to obtain polystyrene particles with a particle size of about 2.1±0.1mm.
[0052] Step 2: Take aerated concrete particles with a particle size of about 4±0.5mm, pass them through a 5-mesh sieve, and then place them at 600±10℃ for 1h, cool them and set them aside; take polystyrene particles, immerse them in silica sol for 20min, take them out and dry them for later use.
[0053] Step 3: Take 300 parts by mass of silicate cement, 120 parts by mass of fine sand, 120 parts by mass of aerated concrete particles, 75 parts by mass of expanded perlite, 50 parts by mass of polystyrene particles, 10 parts by mass of ethylene vinyl acetate, 3 parts by mass of composite staple fibers, 0.5 parts by mass of water reducer and 0.4 parts by mass of hydroxypropyl methylcellulose ether as raw materials for use; wherein the composite staple fibers include equal masses of 3 mm long polypropylene staple fibers and 10 mm long basalt fibers.
[0054] Step 4: Mix silicate cement, fine sand, hydroxypropyl methyl cellulose ether and water reducer, and stir in a dry powder state for 5 minutes; then add aerated concrete particles, expanded perlite and polystyrene particles in sequence while stirring at a speed of 145 r / min, and continue stirring for 5 minutes after adding the materials; then add ethylene vinyl acetate and composite short fibers, and stir for 10 minutes; finally, add 2% of the total mass of the above raw materials, and stir for 15 minutes to obtain a floor mortar material.
[0055] Example 4
[0056] Step 1: Take a polystyrene masterbatch with a particle size of about 1.5±0.2mm, immerse it in a silane coupling agent KH550 aqueous solution with a mass concentration of 2wt% by volume, ultrasonically treat it for 10 minutes, then take it out and drain it, and then spray a polyvinyl alcohol aqueous solution with a mass concentration of 5wt% on its surface, place it at 80℃ and cure it for 20 minutes to obtain polystyrene particles with a particle size of about 2.1±0.1mm.
[0057] Step 2: Take aerated concrete particles with a particle size of about 4±0.5mm, pass them through a 5-mesh sieve, and then place them at 600±10℃ for 1h, cool them and set them aside; take polystyrene particles, immerse them in silica sol for 20min, take them out and dry them for later use.
[0058] Step 3: Take 300 parts by mass of silicate cement, 120 parts by mass of fine sand, 85 parts by mass of aerated concrete particles, 50 parts by mass of expanded perlite, 45 parts by mass of polystyrene particles, 12 parts by mass of ethylene vinyl acetate, 5 parts by mass of composite staple fibers, 0.5 parts by mass of water reducer and 0.4 parts by mass of hydroxypropyl methylcellulose ether as raw materials for use; wherein the composite staple fibers include equal masses of 3 mm long polypropylene staple fibers and 10 mm long basalt fibers.
[0059] Step 4: Mix silicate cement, fine sand, hydroxypropyl methyl cellulose ether and water reducer, and stir in a dry powder state for 5 minutes; then add aerated concrete particles, expanded perlite and polystyrene particles in sequence while stirring at a speed of 145 r / min, and continue stirring for 5 minutes after adding the materials; then add ethylene vinyl acetate and composite short fibers, and stir for 10 minutes; finally, add 2% of the total mass of the above raw materials, and stir for 15 minutes to obtain a floor mortar material.
[0060] Example 5
[0061] Step 1: Take a polystyrene masterbatch with a particle size of about 1.5±0.2mm, immerse it in a silane coupling agent KH550 aqueous solution with a mass concentration of 2wt% by volume, ultrasonically treat it for 10 minutes, then take it out and drain it, and then spray a polyvinyl alcohol aqueous solution with a mass concentration of 5wt% on its surface, place it at 80℃ and cure it for 20 minutes to obtain polystyrene particles with a particle size of about 2.1±0.1mm.
[0062] Step 2: Take aerated concrete particles with a particle size of about 4±0.5mm, pass them through a 5-mesh sieve, and then place them at 600±10℃ for 1h, cool them and set them aside; take polystyrene particles, immerse them in silica sol for 20min, take them out and dry them for later use.
[0063] Step 3: Take 300 parts by mass of silicate cement, 120 parts by mass of fine sand, 115 parts by mass of aerated concrete particles, 50 parts by mass of expanded perlite, 32 parts by mass of polystyrene particles, 8 parts by mass of ethylene vinyl acetate, 1.5 parts by mass of composite staple fibers, 0.5 parts by mass of water reducer and 0.4 parts by mass of hydroxypropyl methylcellulose ether as raw materials for use; wherein the composite staple fibers include equal masses of 3 mm long polypropylene staple fibers and 10 mm long basalt fibers.
[0064] Step 4: Mix silicate cement, fine sand, hydroxypropyl methyl cellulose ether and water reducer, and stir in a dry powder state for 5 minutes; then add aerated concrete particles, expanded perlite and polystyrene particles in sequence while stirring at a speed of 145 r / min, and continue stirring for 5 minutes after adding the materials; then add ethylene vinyl acetate and composite short fibers, and stir for 10 minutes; finally, add 2% of the total mass of the above raw materials, and stir for 15 minutes to obtain a floor mortar material.
[0065] Example 6
[0066] Step 1: Take a polystyrene masterbatch with a particle size of about 1.0±0.2mm, immerse it in a silane coupling agent KH550 aqueous solution with a mass concentration of 2wt% by volume, ultrasonically treat it for 10 minutes, then take it out and drain it, and then spray a polyvinyl alcohol aqueous solution with a mass concentration of 5wt% on its surface, place it at 80℃ and cure it for 20 minutes to obtain polystyrene particles with a particle size of about 1.2±0.1mm.
[0067] Step 2: Take aerated concrete particles with a particle size of about 1±0.3 mm, pass them through a 5-mesh sieve, and then place them at 600±10°C for calcination for 1 hour. Cool them and set them aside. Take polystyrene particles, immerse them in silica sol for 20 minutes, take them out and dry them for later use.
[0068] Step 3: Take 300 parts by mass of silicate cement, 120 parts by mass of fine sand, 100 parts by mass of aerated concrete particles, 60 parts by mass of expanded perlite, 40 parts by mass of polystyrene particles, 10 parts by mass of ethylene vinyl acetate, 3 parts by mass of composite staple fibers, 0.5 parts by mass of water reducer and 0.4 parts by mass of hydroxypropyl methylcellulose ether as raw materials for use; wherein the composite staple fibers include equal masses of 3 mm long polypropylene staple fibers and 10 mm long basalt fibers.
[0069] Step 4: Mix silicate cement, fine sand, hydroxypropyl methyl cellulose ether and water reducer, and stir in a dry powder state for 5 minutes; then add aerated concrete particles, expanded perlite and polystyrene particles in sequence while stirring at a speed of 145 r / min, and continue stirring for 5 minutes after adding the materials; then add ethylene vinyl acetate and composite short fibers, and stir for 10 minutes; finally, add 2% of the total mass of the above raw materials, and stir for 15 minutes to obtain a floor mortar material.
[0070] Comparative Example 1
[0071] The difference between this comparative example and Example 1 is that aerated concrete particles, polystyrene particles and nano-silica particles are not included, and the preparation method includes the following steps:
[0072] Step 1: Take 300 parts by mass of silicate cement, 120 parts by mass of fine sand, 60 parts by mass of expanded perlite, 10 parts by mass of ethylene vinyl acetate, 3 parts by mass of composite staple fibers, 0.5 parts by mass of water reducer and 0.4 parts by mass of hydroxypropyl methylcellulose ether as raw materials for standby use; wherein the composite staple fibers include equal masses of 3 mm long polypropylene staple fibers and 10 mm long basalt fibers.
[0073] Step 4: Mix silicate cement, fine sand, hydroxypropyl methyl cellulose ether and water reducer, and stir in dry powder state for 5 minutes; then add granular expanded perlite in sequence while stirring at a speed of 145r / min, and continue stirring for 5 minutes after adding the materials; then add ethylene vinyl acetate and composite short fiber, stir for 15 minutes, and obtain mortar material.
[0074] Comparative Example 2
[0075] The difference between this comparative example and Example 1 is that aerated concrete particles and polystyrene particles are not included, and the preparation method includes the following steps:
[0076] Step 1: Take 300 parts by mass of silicate cement, 120 parts by mass of fine sand, 60 parts by mass of expanded perlite, 10 parts by mass of ethylene vinyl acetate, 3 parts by mass of composite staple fibers, 0.5 parts by mass of water reducer and 0.4 parts by mass of hydroxypropyl methylcellulose ether as raw materials for standby use; wherein the composite staple fibers include equal masses of 3 mm long polypropylene staple fibers and 10 mm long basalt fibers.
[0077] Step 4: Mix silicate cement, fine sand, hydroxypropyl methyl cellulose ether and water reducer, and stir in a dry powder state for 5 minutes; then add granular expanded perlite in sequence while stirring at a speed of 145 r / min, and continue stirring for 5 minutes after adding the materials; then add ethylene vinyl acetate and composite short fiber, and stir for 10 minutes; finally, add 2% of the total mass of the above raw materials, and stir for 15 minutes to obtain a mortar material.
[0078] Comparative Example 3
[0079] The difference between this comparative example and Example 1 is that the amount of aerated concrete particles is different. The preparation method includes the following steps:
[0080] Step 1: Take a polystyrene masterbatch with a particle size of about 1.5±0.2mm, immerse it in a silane coupling agent KH550 aqueous solution with a mass concentration of 2wt% by volume, ultrasonically treat it for 10 minutes, then take it out and drain it, and then spray a polyvinyl alcohol aqueous solution with a mass concentration of 5wt% on its surface, place it at 80℃ and cure it for 20 minutes to obtain polystyrene particles with a particle size of about 2.1±0.1mm.
[0081] Step 2: Take aerated concrete particles with a particle size of about 4±0.5mm, pass them through a 5-mesh sieve, and then place them at 600±10℃ for 1h, cool them and set them aside; take polystyrene particles, immerse them in silica sol for 20min, take them out and dry them for later use.
[0082] Step 3: Take 300 parts by mass of silicate cement, 120 parts by mass of fine sand, 20 parts by mass of aerated concrete particles, 60 parts by mass of expanded perlite, 40 parts by mass of polystyrene particles, 10 parts by mass of ethylene vinyl acetate, 3 parts by mass of composite staple fibers, 0.5 parts by mass of water reducer and 0.4 parts by mass of hydroxypropyl methylcellulose ether as raw materials for use; wherein the composite staple fibers include equal masses of 3 mm long polypropylene staple fibers and 10 mm long basalt fibers.
[0083] Step 4: Mix silicate cement, fine sand, hydroxypropyl methyl cellulose ether and water reducer, and stir in a dry powder state for 5 minutes; then add aerated concrete particles, expanded perlite and polystyrene particles in sequence while stirring at a speed of 145 r / min, and continue stirring for 5 minutes after adding the materials; then add ethylene vinyl acetate and composite short fibers, and stir for 10 minutes; finally, add 2% of the total mass of the above raw materials, and stir for 15 minutes to obtain a floor mortar material.
[0084] Comparative Example 4
[0085] The difference between this comparative example and Example 1 is that the amount of polystyrene particles used is different. The preparation method includes the following steps:
[0086] Step 1: Take a polystyrene masterbatch with a particle size of about 1.5±0.2mm, immerse it in a silane coupling agent KH550 aqueous solution with a mass concentration of 2wt% by volume, ultrasonically treat it for 10 minutes, then take it out and drain it, and then spray a polyvinyl alcohol aqueous solution with a mass concentration of 5wt% on its surface, place it at 80℃ and cure it for 20 minutes to obtain polystyrene particles with a particle size of about 2.1±0.1mm.
[0087] Step 2: Take aerated concrete particles with a particle size of about 4±0.5mm, pass them through a 5-mesh sieve, and then place them at 600±10℃ for 1h, cool them and set them aside; take polystyrene particles, immerse them in silica sol for 20min, take them out and dry them for later use.
[0088] Step 3: Take 300 parts by mass of silicate cement, 120 parts by mass of fine sand, 100 parts by mass of aerated concrete particles, 60 parts by mass of expanded perlite, 10 parts by mass of polystyrene particles, 10 parts by mass of ethylene-vinyl acetate, 3 parts by mass of composite staple fibers, 0.5 parts by mass of water reducer and 0.4 parts by mass of hydroxypropyl methylcellulose ether as raw materials for use; wherein the composite staple fibers include equal masses of 3 mm long polypropylene staple fibers and 10 mm long basalt fibers.
[0089] Step 4: Mix silicate cement, fine sand, hydroxypropyl methyl cellulose ether and water reducer, and stir in a dry powder state for 5 minutes; then add aerated concrete particles, expanded perlite and polystyrene particles in sequence while stirring at a speed of 145 r / min, and continue stirring for 5 minutes after adding the materials; then add ethylene vinyl acetate and composite short fibers, and stir for 10 minutes; finally, add 2% of the total mass of the above raw materials, and stir for 15 minutes to obtain a floor mortar material.
[0090] Test example
[0091] The floor mortar materials prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were taken as samples, and the following performance tests were performed:
[0092] (1) Based on the requirements for floor impact sound insulation specified in GB / T 50118-2010 "Code for Design of Sound Insulation for Civil Buildings", and in accordance with Part 6: Laboratory Measurement of Floor Impact Sound Insulation in GB / T 19889.6-2005 "Measurement of Sound Insulation of Acoustic Buildings and Building Elements", the impact sound insulation effects of the above samples were measured and compared. The results are summarized in Table 1 below:
[0093] Table 1 Impact sound insulation test results of different samples
[0094]
[0095] (2) According to the relevant requirements of GB / T 29756-2013 "Test method for flexural and compressive strength of hardened mortar", JGJ 110-97 "Test standard for bond strength of facing tiles in building engineering", and JGJ / T 70-2009 "Test method standard for basic properties of building mortar", the mechanical material properties of the above samples were measured. The results are summarized in Table 2 below:
[0096] Table 2 Mechanical properties of different samples
[0097]
[0098]
[0099] In summary, through the results of the measurements of Examples 1-6 and Comparative Examples 1-4, it can be found that the samples in Examples 1 to 6 show significantly stronger comprehensive performance effects in terms of sound insulation effect and material mechanical properties. This shows that the mortar material and preparation method thereof proposed in the present invention for floor sound insulation and thermal insulation can more effectively insulate and absorb the impact sound required between floor slabs. It is different from the propagation path and sound insulation mechanism of airborne sound, and achieves a stronger impact sound insulation effect through a lighter and more elastic mortar material. At the same time, the synergistic effect between the component materials is used to enhance the bonding strength and mechanical strength of the mortar material system, so that it can have stronger crack resistance and durability in practical applications.
[0100] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention shall be included within the scope of protection of the present invention.
Claims
1. A mortar material used for sound insulation and thermal insulation of floor slabs, characterized in that: Calculated by mass, it includes 250-350 parts of silicate cement, 100-150 parts of fine sand, 80-120 parts of aerated concrete particles, 50-80 parts of expanded perlite, 30-50 parts of polystyrene particles, 8-12 parts of redispersible latex powder, 1-5 parts of composite short fibers, 0.5-1 parts of water reducing agent, and 0.3-0.5 parts of cellulose; The particle size of the aerated concrete particles is 0.5-5 mm, and the particle size of the polystyrene particles is 1-3 mm.
2. The mortar material for floor sound insulation and thermal insulation according to claim 1, characterized in that: The polystyrene particles are made from polystyrene masterbatch through surface strengthening treatment, and the preparation method comprises the following steps: The polystyrene masterbatch is immersed in a silane coupling agent aqueous solution and ultrasonically treated; after being taken out and drained, a polyvinyl alcohol aqueous solution is sprayed on the surface and solidified into a film to obtain the polystyrene particles.
3. The mortar material for floor sound insulation and thermal insulation according to claim 1, characterized in that: The composite short fibers include polypropylene fibers and basalt fibers, wherein the length of the polypropylene short fibers is 3-6 mm, and the length of the basalt fibers is 8-12 mm.
4. The mortar material for floor sound insulation and thermal insulation according to claim 3, characterized in that: The mass ratio of polypropylene fiber to basalt fiber is 1:1-3.
5. A method for preparing a mortar material for floor sound insulation and thermal insulation according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1 Mix silicate cement, fine sand, cellulose and water reducer according to the amount and stir the dry powder; S2 then adds aerated concrete particles, expanded perlite particles and polystyrene in sequence while stirring, and continues stirring after the addition is completed; S3 then adds the redispersible latex powder and composite short fibers and stirs; Finally, S4 adds nano-silicon dioxide particles and stirs to obtain the mortar material used for floor sound insulation and heat preservation.
6. The method for preparing a mortar material for floor sound insulation and thermal insulation according to claim 5, characterized in that: In step S2, the aerated concrete particles are pre-treated as follows before being added: Take aerated concrete particles, crush and screen them, and then calcine them at 500-700℃ for 0.5-2h for standby use.
7. The method for preparing a mortar material for floor sound insulation and thermal insulation according to claim 5, characterized in that: In step S2, the polystyrene is pretreated as follows before being added: Take polystyrene particles, impregnate them with silica sol, dry them into a film, and set aside.
8. The method for preparing a mortar material for floor sound insulation and thermal insulation according to claim 5, characterized in that: In step S4, the nano-silicon dioxide particles account for 1-3% of the total material mass.
Citation Information
Patent Citations
Composite heat preservation and sound insulation floor system and construction method thereof
CN119411773A